Field experiments on food choice in grocery stores: A 'how-to' guide. (August 2018) - Carroll, Kathryn A.; Samek, Anya
Highlights: Grocery store field experiments can be useful to learn about purchasing behaviors. We provide a 'how-to' guide for researchers. Three case studies examine the process of forming retail-research partnerships. We also discuss best practices for study design and implementation. Abstract: Food choice is an important area of study, as habitual consumption of high sugar, high fat, and low nutrient foods has been shown to contribute to obesity and related chronic conditions. Grocery stores and supermarkets play a particularly important role in food choice, since they account for almost half of all retail food sales. We propose that conducting field experiments in grocery stores is an attractive methodology for learning about food purchasing behaviors and identifying policy levers that may be successful in shaping those behaviors. We summarize the challenges and barriers that researchers may face while carrying out field experiments in a retail grocery environment, and provide a simple 'how-to' guide that researchers can use to replicate field experiment best practices in this setting.